2018
DOI: 10.1002/tox.22659
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term exposure to extremely low‐dose of nicotine and 4‐(methylnitrosamino)‐1‐(3‐pyridyl)‐1‐butanone (NNK) induce non‐malignant breast epithelial cell transformation through activation of the a9‐nicotinic acetylcholine receptor‐mediated signaling pathway

Abstract: Breast cancer (BC) is the most common cancer affecting women worldwide and has been associated with active tobacco smoking. Low levels of nicotine (Nic) and 4‐(methylnitrosamino)‐1‐(3‐pyridyl)‐1‐butanone (NNK), have been detected in cases of second‐hand smoke (SHS). However, the correlation between SHS and BC risk remains controversial. In this study, we investigated whether the physiological SHS achievable dose of Nic and tobacco specific nitrosamine, NNK act together to induce breast carcinogenesis using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Many studies indicate that nicotine induces breast cancer growth and metastasis in vitro and in vivo through binding to and activating α9-nAChR [20,23,30,31]. Long-term exposure to extremely low doses of nicotine and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) induced nonmalignant breast epithelial cell transformation through activation of the α9-nAChR-mediated signaling pathways [32]. However, the mechanisms by which nicotine-induced α9-nAChR activity promotes melanoma growth and metastasis are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies indicate that nicotine induces breast cancer growth and metastasis in vitro and in vivo through binding to and activating α9-nAChR [20,23,30,31]. Long-term exposure to extremely low doses of nicotine and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) induced nonmalignant breast epithelial cell transformation through activation of the α9-nAChR-mediated signaling pathways [32]. However, the mechanisms by which nicotine-induced α9-nAChR activity promotes melanoma growth and metastasis are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…As it is still debated whether exposure to second-hand smoke (SHS) affects the risk of breast cancer, Fararjeh et al (2019) used a model of breast cell carcinogenesis in which immortalized normal human breast epithelial cells exposed to a carcinogen undergo long-term exposure to 1 pM nicotine and/or 100 femtM NNK doses (that can be reached during exposure to SHS). They found that repeated co-exposure to nicotine and NNK disrupted cell growth control and led to the acquisition of cancer cell properties, and increased the levels of a number of α9 nAChR downstream signaling proteins, such as the FAK migration marker and the PI3K/Akt intracellular signaling pathway.…”
Section: α9-mediated Effects Of Nicotine On Breast Cancer Cellsmentioning
confidence: 99%
“…Indeed, the interaction of nicotine and its derivatives with nAChRs has been well linked to the development of many types of cancers 144 . In particular, a number of studies have shown that exposure to nicotine or NNK induces malignant transformation of normal breast epithelial cells and promotes proliferation and metastasis of BC cells 145 . This is supported by epidemiological findings that cigarette smoking is associated with increased BC risk.…”
Section: Introductionmentioning
confidence: 99%